Public debt and private firm funding: Evidence from Chinese cities - Yi Huang; Marco Pagano; Ugo Panizza (Graduate Institute of International and Development Studies, 2016)
In China, local public debt issuance between 2006 and 2013 crowded out investment by private manufacturing firms by tightening their funding constraints, while it did not affect state-owned and foreign firms. Using novel data for local public debt issuance, we establish this result in three ways. First, local public debt is inversely correlated with the city-level investment ratio of domestic private manufacturing firms. Instrumental variable regressions indicate that this link is causal. Second, local public debt has a larger negative effect on investment by private firms in industries more dependent on external funding. Finally, in cities with high government debt, firm-level investment is more sensitive to internal funding, also when this sensitivity is estimated jointly with the firm's likelihood of being credit-constrained. Altogether, these results suggest that, by curtailing private investment, the massive public debt issuance associated with the post-2008 fiscal stimulus sapped long-term growth prospects in China.
Keywords: E22; H63; H74; L60; O16; 330; Investment; Local public debt; Crowding out; Credit constraints; China